Transferable Skills-Based Career Guidance to Increase Student Career Maturity - Ayong Lianawati; Muwakhidah; Ahmad Rofi Suryahadikusumah; Fifi Khoirul Fitriyah; Irfan Fahriza (South Sulawesi Education Development (SSED), 2024)
Career guidance based on transferable skills is needed so that students do not limit their career choices and are more confident in their career choices. Transferable skills are general skills needed to survive in today's world of work, and is part of the Sustainable Development Goals (SDGs) formulated by UNICEF.. The research aims to design and test a career guidance program containing transferable skills to increase student career maturity. A quantitative approach was used in this research; the method used was a quasi-experiment. The research was conducted on FKIP Universitas PGRI Adibuana Semester 8 students. The research sample will be chosen randomly, taking 20% of the research population. Data collection uses two tools: Transferable Skills Analysis and Career Maturity Scale. Research shows a significant change in student career maturity. The t-test results meet the H0 rejection criteria. Sig value. (2-tailed) = 0.00 and tstat = 59.500, indicating transferable skills-based career guidance effectively increases student career maturity. Research recommends that universities should be concerned about developing students' transferable skills in lecture programs and extracurricular activities in training, internships, and industry-based learning.